Assessment of Enteropathogens from Fresh Vegetables Associated Serious Risks to Human Health - Sharnagat, P.; Jaiswal, K.P. (International Journal of Scientific Research in Biological Sciences, 2023)
The general public has become increasingly interested in eating fresh vegetables all over the world; microbiologically unsafe vegetables are a persistent public health issue in developing countries, including India. The goals of this study were to assess infection risks from enteropathogens for raw vegetable consumers in different geographical locations in Madhya Pradesh, India, as well as to evaluate effectiveness, pathogenecity, and infection risks. To achieve the objectives, samples were collected from different locations in Madhya Pradesh, India. The findings indicate that regular consumption of fresh, raw vegetables sold on the street would be harmful due to the presence of enteropathogens. Though the immunity of Indians is considered high, regular intake of such contaminated vegetables would detoriate the individual`s health.